Keeping Journal Writing To Improve The Writing Ability Of The Tenth Grade Students Of Man Aek Natas In The Academic Year 2020/2021 - Ikrar Saputra (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
Since years ago, people often think that writing is the most difficult skill. Limited in grammar, difficult in word choice and afraid in making mistakes are some reasons why writing viewed as difficult skill. These also made most of the students on MAN Aek Natas Labuhanbatu Utara that has good facilities in support the English learning process precisely has a low ability in writing that proved by the score of 52, 4 under the KKM score. This research is conduct to improve the writing ability of the tenth grade students MAN Aek Natas Labuhanbatu Utara by keeping journal. The purpose of this research is describes whether there is or no significance progress in the students writing ability of the tenth grade students of MAN Aek Natas Labuhanbatu UtaraKudus after keeping journal writing. This study belongs to experimental research with pre-test and post-test design. This study focus on applying journal writing to the tenth grade students of MAN Aek Natas Labuhanbatu Utara based on learning journal on Hiemstra (2001) concept and adding by the writer’s own develop. After getting treatment, students are tested in the post-test. The result of post test showed that the students stand on the categorize of “Good” from the mean score 58,2 into 80,5 with to 8,04 > tt 2,04 on the level of significance 5% and degree of freedom 34 (n-1).